Evaluation of the Manila Science High School library collection based on curricular requirements - Soliman, Marishiel A. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
The collection of the school library is largely based on the curriculum offered by its institution. To determine if the MSHS library adequately supports the curriculum of the school, the researcher evaluated the book collection through collection mapping based on the schools' curriculum. Through this, the total number of titles and a volume per subject was determined.